Management Accounting Standards for Sustainable Business Practices - Oncioiu, Ionica (IGI Global, 2019)
Modern companies are under increasing pressure to conduct their business in an environmentally responsible manner due to social and environmental problems. They must find the means to deploy their businesses in a socially- and environmentally-sustainable way without sacrificing their economic performance (e.g., profits to shareholders and owners) and wellbeing. By integrating multiple processes and methods, management accounting plays a key role in achieving a company's sustainability, notably by providing reliable, relevant, accurate, and timely information to managers. Management Accounting.